Justice, crime, and ethics - Braswell, Michael; McCarthy, Bernard J.; McCarthy, Belinda Rodgers (Routledge/Taylor & Francis Group, 2017)
Justice, Crime, and Ethics, a leading textbook in criminal justice programs, examines ethical dilemmas pertaining to the administration of criminal justice and professional activities in the field. This ninth edition continues to deliver a broad scope of topics, focusing on law enforcement, legal practice, sentencing, corrections, research, crime control policy, and philosophical issues.